2004
DOI: 10.1023/b:joec.0000028433.67396.93
|View full text |Cite
|
Sign up to set email alerts
|

New Type of Sesiidae Sex Pheromone Identified from the Hornet Moth Sesia apiformis

Abstract: Two components of the female-produced sex pheromone of the hornet moth, Sesia apiformis, were identified as (3Z,13Z)-octadeca-3,13-dien-1-ol (3Z,13Z-18:OH) and (2E,13Z)-octadeca-2,13-dienal (2E,13Z-18:Al), a pheromone structure new in Sesiidae. Pooled gland extracts showed the two major compounds in a proportion of ca. 2:3, while SPME-investigations on single calling females revealed a ratio of ca. 1:7. Although the single compounds were not attractive, a 2:3 mixture proved to be highly active towards males in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 5 publications
0
21
0
Order By: Relevance
“…These two components have been identified in SPME collections and solvent extracts, but their relative ratios are markedly different from each other. Differences in pheromone composition between gland extracts and female volatiles have been reported from other moths, including Sesia apiformis (Francke et al, 2004), Marmara gulosa (McElfresh et al, 2009), and Spodoptera exigua (Acín et al, 2010), showing that this discrepancy is usual in the Lepidoptera. The considerable variability in relative ratio and small amount of Z3-12:OAc and Z5-12:OAc recovered from SPME samples may be attributable to the degradation and/or adsorption of acetate components by the moth bodies, the loose scales, and adsorption to the walls of the container during overnight collections, as observed in other moths (Baker et al, 1980;Millar and Rice, 1992).…”
Section: Discussionmentioning
confidence: 81%
“…These two components have been identified in SPME collections and solvent extracts, but their relative ratios are markedly different from each other. Differences in pheromone composition between gland extracts and female volatiles have been reported from other moths, including Sesia apiformis (Francke et al, 2004), Marmara gulosa (McElfresh et al, 2009), and Spodoptera exigua (Acín et al, 2010), showing that this discrepancy is usual in the Lepidoptera. The considerable variability in relative ratio and small amount of Z3-12:OAc and Z5-12:OAc recovered from SPME samples may be attributable to the degradation and/or adsorption of acetate components by the moth bodies, the loose scales, and adsorption to the walls of the container during overnight collections, as observed in other moths (Baker et al, 1980;Millar and Rice, 1992).…”
Section: Discussionmentioning
confidence: 81%
“…Although previous studies have reported a few catches of RCB with (3E,13Z)-18:OH (Solomon et al 1982;Brown and Snow 1985), we did not capture a single moth in traps baited with this alcohol or the acetate analogue ( Table 2). Failure of any lure except (3E,13Z)-18:Ald to attract male moths negated the need for statistical analysis in experiment 1, and clearly indicated that the RCB sex pheromone has an aldehyde functionality, which is rare among sesiid moths (Francke et al 2004). Results of experiment 2 revealed the importance of the double bonds at C3 and C13 in (3E,13Z)-18:Ald because (2E,13Z)-18:Ald proved to be unattractive (Table 2).…”
Section: Resultsmentioning
confidence: 99%
“…Note that the temperature programme (see Table 1) differed from that of Figure 1. indicate that (3E,13Z)-18:Ald is the major and perhaps only pheromone component in P. marginata. Single-component pheromones are unusual in Lepidoptera, and even Sesia apiformis (Clerck) (Lepidoptera: Sesiidae), the only sesiid moth known to use an aldehyde pheromone component (El-Sayed 2009), only responds to (2E,13Z)-18:Ald when combined with (3E,13Z)-18:OH (Francke et al 2004). To the best of our knowledge, P. marginata is the only sesiid species currently known to use (3E,13Z)-18:Ald as a pheromone component, and the only sesiid species known to respond to an aldehyde alone.…”
Section: Resultsmentioning
confidence: 99%
“…In general, pheromones emitted by females are effective over longer ranges than those emitted by males (Cardé and Baker 1984). In addition to nocturnal moths, some diurnal moths (families Sesiidae and Zygaenidae) use species-specific sex pheromones (Zagatti and Renou 1984;Koshio and Hidaka 1995;Tanaka and Koshio 2002;Francke et al 2004;Naka et al 2007). These reports and this study suggest that sex pheromones play a predominant role in mating behavior in both nocturnal and diurnal moths.…”
Section: Discussionmentioning
confidence: 99%